DEMOKRASI DAN PEMENUHAN HAK-HAK PEREMPUAN DALAM POLITIK - qamariah, syarifah (An - Nisa`, 2016)
This paper examines democracy and fulfillment of the rights of women in politics. Democracy is based on the principle of popular sovereignty which implies that all people basically have the freedom and the rights and obligations of the same. Democracy in Indonesia, however, we can not be separated from the flow of periodization of political history in Indonesia include; future government period of revolution, parliamentary government (representative demokracy), Government of Guided Democracy (guided demokracy) The New Order (Pancasila Democracy), and the Reformation to the present.A political party is one container women can take part in politics or in other words to increase womens political empowerment. The fulfillment of womens rights in political parties in Indonesia have proven many Indonesian women become MPs and even the history of Indonesian politics have noted and proved that Megawati never become the first woman President of the Republic of Indonesia